Universal Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) Testing Uptake in the Labor and Delivery Unit: Implications for Health Equity. Issue 6 (December 2020) - Kernberg, Annessa; Kelly, Jeannie; Nazeer, Sarah; Russell, Sharman; Tuuli, Methodius; Stout, Molly J.; Raghuraman, Nandini; Carter, Ebony B.
Abstract : OBJECTIVE: To understand severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing uptake in the labor and delivery unit and rationales for declining testing, and to institute a process to increase equitable testing uptake. METHODS: We conducted a quality-improvement initiative from May 28–June 25, 2020, during the first 4 weeks of universal SARS-CoV-2 testing in the Barnes-Jewish Hospital labor and delivery unit. All consecutive patients presenting for delivery without coronavirus disease 2019 (COVID-19) symptoms were offered testing over four 1-week phases. Phase I documented the rate of testing uptake. Phase II recorded patients' reasons for declining testing. Phase III used phase II findings to create and implement shared decision-making tools. Phase IV offered each patient who declined nasopharyngeal testing an oropharyngeal alternative. The primary outcome was rate of SARS-CoV-2 testing uptake by phase. RESULTS: Of 270 patients, 223 (83%) accepted testing and 47 (17%) declined. Maternal age and mode of delivery were similar between groups, whereas testing uptake was higher among nulliparous, White, Hispanic, or privately insured patients. There was a significant increase in the primary outcome of SARS-CoV-2 testing across phases I–IV, from 68% to 76% to 94% to 95%, respectively (Somers' D 0.45; 95% CI of association 0.30–0.59). The most commonly cited reason for declining testing was concern regarding testing discomfort. In subgroup analyses by race and insurance type, there was a significant increase in testing uptake across phases I–IV for Black patients (56%, 54%, 91%, 92%; Somers' D 0.36; 95% CI of association 0.28–0.64), White patients (76%, 93%, 96%, 100%; Somers' D 0.59; 95% CI of association 0.38–0.8), those with Medicaid insurance (60%, 64%, 88%, 92%; 95%; Somers' D 0.39; CI of association 0.22 to 0.56), and those with private insurance (77%, 96%, 97%, 100%; Somers' D 0.63; 95% CI of association 0.40–0.86). CONCLUSION: Universal SARS-CoV-2 testing uptake significantly increased through a rapid-cycle improvement initiative. Aligning hospital policy with patient-centered approaches led to nearly universally acceptable testing. Abstract : Universal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing uptake significantly increased through an initiative aligning hospital policy with patient-centered approaches to promote nearly universal testing acceptability.